2015
DOI: 10.1016/j.ccell.2015.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Taxane Resistance in Prostate Cancer Mediated by AR-Independent GATA2 Regulation of IGF2

Abstract: GATA2 has been well-characterized as a critical pioneer transcription factor for androgen receptor (AR) in prostate cancer. In this issue of Cancer Cell, Vidal and colleagues identify increased GATA2 and its AR-independent transactivation of IGF2 as a mechanism that can mediate taxane resistance through activation of IGF1/insulin receptor signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 10 publications
(11 reference statements)
0
17
0
Order By: Relevance
“…25,26 Therefore, some degree of cross-resistance has been suggested between AR-targeting therapies and taxane chemotherapies, although this cross-resistance may be less substantial with cabazitaxel than with docetaxel. 27 Recently, work on a particular mouse model of CRPC has also suggested that certain AR-Vs may be associated with sensitivity to taxanes whereas others may mediate taxane resistance.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Therefore, some degree of cross-resistance has been suggested between AR-targeting therapies and taxane chemotherapies, although this cross-resistance may be less substantial with cabazitaxel than with docetaxel. 27 Recently, work on a particular mouse model of CRPC has also suggested that certain AR-Vs may be associated with sensitivity to taxanes whereas others may mediate taxane resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, our study revealed a mechanism for conferring multipotentiality to a progenitor cell population that yields erythroid and myeloid cell progeny. The gene controlled by the −77 element, GATA2 , regulates the development of non–small cell lung cancer ( 50 ), aggressive prostate cancer ( 51 ), primary immunodeficiency, MDS, and myeloid leukemia ( 16 , 44 ). GATA2 is also linked to the development/function of the pituitary ( 52 ) and important components of the nervous system ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that IGF2 encodes a member of the insulin family of polypeptide growth factors, which promote growth-promoting activity possess. Consequently, as an antisense RNA of IGF2, IGF2-AS plays an important role in various cancers, including neuroblastoma and prostate cancer [34,35]. However, the function of IGF2-AS in thyroid carcinoma has not been elucidated yet; larger cohort is needed to testify the role and mechanisms.…”
Section: Lab/in Vitro Researchmentioning
confidence: 99%